Copper nanoparticles mediated physiological changes and transcriptional variations in microRNA159 (miR159) and mevalonate kinase (MVK) in pepper; potential benefits and phytotoxicity assessment. Issue 5 (October 2021) - Tabatabaee, Shiva; Iranbakhsh, Alireza; Shamili, Mansoore; Oraghi Ardebili, Zahra
Abstract: The cytotoxicity assessment of nanomaterials has become a global concern for diverse disciplines, including agriculture. This study explored the physiological and molecular responses of pepper seedlings to the foliar application of copper nanoparticles (CuNPs; 50, 100, and 200 mg L −1 ) compared to the bulk control. The CuNPs treatment at 50 mg L −1 increased the shoot biomass by 20%, whereas the treatments at concentrations above 100 mg L −1 adversely influenced biomass (25%), chlorophyll content (21%), and starch concentration (23%). Moreover, the CuNPs treatments at the toxic doses increased H2 O2 concentration (60%) and lipid peroxidation levels (27%), implying oxidative stress and potentially impaired membrane integrity. However, the phytotoxicity risk associated with the CuNPs application was lower than the bulk control. The CuNPs treatments upregulated the activities of catalase (2-folds), peroxidase (85%), and polyphenol oxidase (70%). The toxic doses of CuNPs increased the protease activity by 16%. The Cu supplementation influenced the transcription of microRNA159 ( miR159 ) and Mevalonate kinase ( MVK ) genes in concentration and material type-dependent manners. Toxic concentrations of CuNP transcriptionally upregulated miR159 by approximately 2-folds. The expression of the MVK gene displayed a downregulation trend (5-folds) in response to the bulk Cu, while the CuNPs treatments slightly downregulated this gene. With increasing the concentration of CuNPs, the accumulations of protein and non-protein thiols displayed an increasing trend by approximately 45%. The CuNPs-treated plants contained a higher concentration of proline (59%) and phenols (34%). This study underlines the potential cytotoxicity risk associated with the application of CuNPs as a fertilizer or pesticide in agriculture-related industries. Graphical Abstract: ga1 Highlights: Representing potential benefits and phytotoxicity of copper nanoparticle (CuNP). Toxic concentrations of CuNP transcriptionally upregulated miR159. CuNP down-regulated transcription of MVK gene involved in terpenoid metabolism. Providing evidence on the correlation between developmental transition and miR159. The phytotoxicity risk of CuNP was lower than the bulk counterpart.